2022
DOI: 10.53550/eec.2022.v28i01.042
|View full text |Cite
|
Sign up to set email alerts
|

Split application of GA3: Effective to improve growth, yield and quality of cape gooseberry (Physalis peruviana L.)

Abstract: Livestock emit large quantities of methane as part of their natural digestive processes. Livestock is a significant source of methane, a potent greenhouse gas, in agriculture. Carbon dioxide is much more abundant than methane in the atmosphere. Methane, on the other hand, traps 30 times more heat than carbon dioxide. Methane (CH4) is the main component of natural gas and a powerful greenhouse gas (GHG). After escaping into the atmosphere, greenhouse gases act as a shield, insulating the Earth and trapping ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Our results are consistent with those of Kaur et al [1], who demonstrated the significant impact of GA3 on enhancing the size and weight of Cape gooseberry fruits. Furthermore, Singh et al [31] reported that applying GA3 during different stages, such as vegetative, flowering, and fruit-setting, significantly improved the yield of Cape gooseberry fruits. Moreover, tendentially, three levels of GA3 (150, 200, and 250) significantly increased the total soluble solids (TSS) in fruits, suggesting an improvement in fruit quality (Table 3).…”
Section: Effects Of Ga3 Levels On Plant Generative Development Parame...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with those of Kaur et al [1], who demonstrated the significant impact of GA3 on enhancing the size and weight of Cape gooseberry fruits. Furthermore, Singh et al [31] reported that applying GA3 during different stages, such as vegetative, flowering, and fruit-setting, significantly improved the yield of Cape gooseberry fruits. Moreover, tendentially, three levels of GA3 (150, 200, and 250) significantly increased the total soluble solids (TSS) in fruits, suggesting an improvement in fruit quality (Table 3).…”
Section: Effects Of Ga3 Levels On Plant Generative Development Parame...mentioning
confidence: 99%
“…The authors attributed this effect to the PGR's ability to accelerate biochemical reactions, increasing TSS content. In addition, Singh et al [31] reported a noteworthy elevation in total soluble solids (TSS) in Cape gooseberry fruits following the application of GA3 foliar spray, compared to the control. The authors attributed this significant change to the higher accumulation of sugars and other soluble compounds or the faster conversion of starch and acids into simple sugars.…”
Section: Effects Of Ga3 Levels On Plant Generative Development Parame...mentioning
confidence: 99%